Evaluation of social cognition, autistic traits, and dysmorphology in comorbid specific learning disorder and attention-deficit/hyperactivity disorder. (October 2022) - Ozbaran, Nazli Burcu; Ozyasar, Senay Celenay; Dogan, Nurhak; Kafali, Helin Yilmaz; Isik, Esra; Satar, Aysegul; Kose, Sezen; Atik, Tahir; Cogulu, Ozgur
Research on areas such as social cognition, autistic traits, and minor physical anomalies in comorbid Specific Learning Disorder (SLD) and attention-deficit/hyperactivity disorder (ADHD) is limited. In this study, we compared these areas in children aged between 8 and 14 with comorbid SLD and ADHD and their typically developed peers. Emotion recognition and social cognition were evaluated by Faces Test, Reading the Mind in the Eyes Test, Comprehension Test, and Difficulties in Emotion Regulation Scale. Autism Spectrum Screening Questionnaire and Social Responsiveness Scale were used for screening of autism spectrum disorder in children. Furthermore, autistic traits in parents were measured by Autism-Spectrum Quotient. The MPAs of all the subjects were determined by pediatric geneticists. We detected that children with comorbid SLD and ADHD performed worse than controls in all social cognition tests and maternal AQ score had a strong correlation with the Faces Test, DERS, and SRS scores. Also, the total ASSQ score in the comorbid SLD and ADHD group was significantly higher than controls. Finally, MPAs were significantly more frequent in the comorbid SLD and ADHD group. Impairment in social cognition and evaluation of autistic traits and dysmorphology in children with comorbid SLD and ADHD may provide useful information on neurodevelopmental disorders.